Synthesis and Biological Activity of Triazole‐Appended N, O‐Nucleosides1. Issue 25 (15th May 2014) - Romeo, Roberto; Giofrè, Salvatore V.; Carnovale, Caterina; Chiacchio, Maria A.; Campisi, Agata; Mancuso, Raffaella; Cirmi, Santa; Navarra, Michele
Abstract: 1, 2, 3‐Triazole‐appended N, O‐nucleosides have been synthesized by an approach combining a 1, 3‐dipolar cycloaddition process and an alkyne–azide click chemistry reaction. Biological assays, performed on six tumor cell lines, revealed the antiproliferative activity of the synthesized compounds. The effect was more evident in the U87MG human glioblastoma cell line. Thus, these nucleoside analogues could be promising scaffolds for the construction of new anticancer agents. Abstract : 1, 2, 3‐Triazole‐appended N, O‐nucleosides have been synthesized by an approach combining a 1, 3‐dipolar cycloaddition and an alkyne–azide click chemistry reaction. The synthesized compounds showed antiproliferative activity against tumor cell lines. These nucleoside analogues could be promising scaffolds for the construction of new anticancer agents.